Peningkatan Kemampuan Membaca Pemahaman Menggunakan Metode SQ3R (Survey, Question, Read, Recite, Review) di Kelas V SDN 06 Pauh Kecamatan Lubuk Sikaping Kabupaten Pasaman - Fadlilah, Miftahul; Suriani, Ari; Sukma, Elfia; Alwi, Nur Azmi (TSAQOFAH, 2025)
This research is motivated by the low reading comprehension ability of students in understanding the text as a whole, especially if the text is complex and uses new vocabulary that is not yet known by the students. The purpose of this study is to describe the improvement of reading comprehension ability using the SQ3R method (Survey, Question, Read, Recite, Review) in class V SDN 06 Pauh, Lubuk Sikaping District, Pasaman Regency. This research is a classroom action research (CAR) using qualitative and quantitative approaches. Two cycles were carried out, where cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. Classroom action research includes four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and students. Data from the study were obtained from the assessment of the Teaching Module, the learning implementation process, and learning outcomes. The data collection techniques used were tests and non-tests. The results of the study showed an increase in: a) The Teaching Module in cycle I obtained an average of 85.71% with good qualifications (B), while in cycle II it obtained an average of 92.85% with very good qualifications (SB), b) Teacher activity in cycle I obtained an average of 82.14% with Good qualifications (B) and increased in cycle II by obtaining an average of 96.42% with very good qualifications (SB), while student activity in cycle I obtained an average of 80.36% with Good qualifications (B), and increased in cycle II by obtaining an average of 92.85% with very good qualifications (SB), c) Assessment of student learning outcomes in cycle I obtained a class average of 80.72 and cycle II increased to 87.26. Based on these results, it is concluded that using the SQ3R method (Survey, Question, Read, Recite, Review) can improve students' reading comprehension skills in learning Indonesian.